Perancangan Sistem Registrasi berdasarkan Estimasi Waktu Penanganan Pasien untuk Mencegah Kerumunan Antrian - Astrid Lestari Tungadi; Erick Alfons Lisangan (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
Along with the increase in population and the development of information technology, it is necessary to have a system that is able to support the process of improving health care. One of the weaknesses of the current health care system is the patient waiting time which is still below the established standard, which is less than 60 minutes. This study designed a patient registration system that can estimate the patient's arrival time based on the input symptoms. The use of QR Code technology and meeting applications helps to support patient registration and consultation. The research methodology uses the waterfall method by involving doctors and patients as data sources. Test results using black boxes indicate that the system is able to categorize patient care as expected. The system has also been able to function well functionally. It takes a process of updating symptoms periodically by doctors so that the system is able to recognize new symptoms that have not been recorded previously. With the estimated arrival time, the queue or crowd of patients in the waiting room can be minimized properly.